2020
DOI: 10.1186/s12889-020-08685-7
|View full text |Cite
|
Sign up to set email alerts
|

The social value of investing in public health across the life course: a systematic scoping review

Abstract: Background: Making the case for investing in public health by illustrating the social, economic and environmental value of public health interventions is imperative. Economic methodologies to help capture the social value of public health interventions such as Social Return on Investment (SROI) and Social Cost-Benefit Analysis (SCBA) have been developed over past decades. The life course approach in public health reinforces the importance of investment to ensure a good start in life to safeguarding a safe, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Grant and Booth (2009) identified 14 different methods for reviewing the literature on a specific topic. However, although scholars have shown compelling examples of reviews such as structured literature review (Cuozzo et al , 2017), scoping review (Ashton et al , 2020) and critical review (Keane et al , 2019), this study implements a systematic literature review as it “seeks to systematically search for, appraise and synthesis research evidence, often adhering to guidelines on the conduct of a review” (Grant and Booth, 2009, p. 94). Additionally, as Gosselin et al (2020) performed in their systematic literature review on SROI in sports, this study also follows the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement (Moher et al , 2009).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Grant and Booth (2009) identified 14 different methods for reviewing the literature on a specific topic. However, although scholars have shown compelling examples of reviews such as structured literature review (Cuozzo et al , 2017), scoping review (Ashton et al , 2020) and critical review (Keane et al , 2019), this study implements a systematic literature review as it “seeks to systematically search for, appraise and synthesis research evidence, often adhering to guidelines on the conduct of a review” (Grant and Booth, 2009, p. 94). Additionally, as Gosselin et al (2020) performed in their systematic literature review on SROI in sports, this study also follows the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement (Moher et al , 2009).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Future research could also explore the practical application of social value methods in Public Health Institutes, such as use of SROI methodologies as the primary tool for capturing and articulating the social value of interventions which are promoted by Public Health Institutes. Although there is existing research which collates social value evidence relevant to public health ( 19 , 20 ), there is a need to progress academic evidence of cases studies in the specialty of public health ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Through stakeholder engagement, the SROI approach defines outcomes, and allows a monetary value to be placed on the non-financial returns on investment by applying proxy values (18). This is particularly relevant for public health policies and interventions, which usually have multiple "soft" and difficult to quantify impacts, such as improving or promoting health, wellbeing and equity of population groups and communities, as well as bringing additional benefits to their living, social, or working environment (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat surprisingly, no previous SROI studies of CSA treatment were located in our search of the literature nor were any identified in a 2020 systemic scoping review [ 19 ]. Overall, we found very few programs aimed at examining child or adolescent mental health more generally.…”
Section: Introductionmentioning
confidence: 99%